2022
DOI: 10.1007/s00415-022-11141-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 fatigue: the contribution of cognitive and neuropsychiatric symptoms

Abstract: Fatigue in its many forms of physical, mental, and psychosocial exhaustion is a common symptom of post-COVID-19 condition, also known as “Long COVID.” Persistent fatigue in COVID-19 patients is frequently accompanied by cognitive dysfunction and neuropsychiatric symptoms; however, less is known about the relationships between these components of post-COVID-19 condition and fatigue itself. Consequently, the present study sought to (1) distinguish the types of fatigue experienced by participants, and (2) investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 36 publications
6
55
2
4
Order By: Relevance
“…Central fatigue has previously been associated with the activity of several brain regions and networks. Specifically, a recent study suggested the involvement of the striatum of the basal ganglia, the dorsolateral prefrontal cortex, the dorsal anterior cingulate, the ventromedial prefrontal cortex, and the anterior insula [40]. Of these regions, the anterior cingulate, ventromedial prefrontal cortex, and anterior insula could have a more prominent role [38,41].…”
Section: Discussionmentioning
confidence: 99%
“…Central fatigue has previously been associated with the activity of several brain regions and networks. Specifically, a recent study suggested the involvement of the striatum of the basal ganglia, the dorsolateral prefrontal cortex, the dorsal anterior cingulate, the ventromedial prefrontal cortex, and the anterior insula [40]. Of these regions, the anterior cingulate, ventromedial prefrontal cortex, and anterior insula could have a more prominent role [38,41].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an association between pain and fatigue, the causal association is not fully clarified( Fishbain et al, 2003 ). These findings demonstrate the need to evaluate different constructs in patients with persistent post-COVID-19 fatigue and understand the factors associated with the physical, mental, and psychological aspects of fatigue( Calabria et al, 2022 ).…”
Section: Physiopathological Mechanism: Neuroinflammation and Fatiguementioning
confidence: 97%
“…Although the pathogenesis of brain fog is not fully understood, it has been linked to neuroinflammation associated with the spread of SARS-CoV-2 to the higher brain centers. Brain fog is thought to primarily arise from the diffusion of inflammation within the olfactory bulbs to other brain regions or, less commonly, from the direct infection of parenchymal brain tissue; systemic inflammation induced by SARS-CoV-2 might also have a role [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%